Beyond chatting: The opportunities and challenges of ChatGPT in medicine and radiology (Editorial) - Lavista Ferres, Juan M.; Weeks, Bill, Linda C. Chu; Rowe, Steven P.; Fishman, Elliot K. (Diagnostic and Interventional Imaging, 2023)
The release of ChatGPT by OpenAI in November 2022 marked a pivotal moment in the introduction of a new generation of artificial intelligence (AI) to the broader public. The “GPT” in ChatGPT stands for “generative pre-trained transformer” and is a language model trained to generate realistic- and natural-sounding language. ChatGPT can generate coherent, grammatically correct text, which represents a significant step forward in AI development and has the potential to revolutionize a range of industries, including medicine and radiology.